Behavioral Factor Analysis of Blood Supplement Tablet Consumption in Adolescent Girls as an Effort to Prevent Stunting - Ida Maya Meika Sari; Dhiny Easter Yanti; Nurul Aryastuti; Khoidar Amirus (Postgraduate, University of Mataram, 2023)
The provision of blood supplement tablets (TTD) for adolescent girls is one of the special interventions being pursued by the government to improve the compliance of adolescent girls in taking blood supplement tablets. The government collaborates with health services and educational institutions in distributing TTD. SMP Negeri 2 Bumi Ratu Nuban is a pilot school in the working area of Puskesmas Inpatient Wates. However, the lack of awareness and support provided makes adolescent girls irregular in consuming TTD. The purpose of this study was to analyze the behavioral factors of blood supplement tablets consumption in adolescent girls in an effort to prevent stunting. This type of analytical observational research with a cross sectional design, the population of all adolescent girls. sampling using total sampling with the number of respondents 117 adolescent girls who have menstruated at SMPN 2 Bumi Ratu Nuban. Data collection using a questionnaire. Data analysis using the Chi-Square test. Based on the results of the chi-square test there is a relationship between knowledge (P-Value= 0.002; OR= 7.5; 95%; CL= 1.93-29), attitude (P-Value= 0.039; OR= 2.42, I= 1.116-5. 252), health worker support (P-Value = 0.003; OR = 3.68; 95%; CI = 1.62-8.36) and parental support (P-Value= 0.000; OR= 8.2; 95%; CI= 3.44-19.6) with the consumption behavior of blood supplement tablets in adolescent girls. It is expected that educational activities and monitoring of my health report card book are carried out continuously by health workers who can involve teachers and parents directly.